2010
DOI: 10.1016/j.jfoodeng.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of impact pressure and bruising of apple fruit using pressure-sensitive film technique

Abstract: a b s t r a c tImpact pressure and bruising of apple fruit were measured by means of a pressure-sensitive film technique, in order to develop methods for assessing and predicting bruising of apples resulting from impact loads during the course of transport and handling. Results of impact tests with apples indicate that when the fruits are dropped from different heights onto different impacting surfaces, the bruise area and volume could be assessed and predicted by regression models based on the impact force ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Bruise size in both package designs increased as the drop height increased. These results agree with the findings in a previous study by Lu et al (2012) who reported that the bruise area and volume increased relative to drop heights and number of drops. The fundamental damage of bruise to apples in packages is energy transformation as some of the kinetic energy of drops is absorbed by bruising (Schoorl and Holt, 1982;Holt and Schoorl, 1984;Jarimopas et al, 2007;Zarifneshat et al, 2010).…”
Section: Bruise Sizesupporting
confidence: 93%
“…Bruise size in both package designs increased as the drop height increased. These results agree with the findings in a previous study by Lu et al (2012) who reported that the bruise area and volume increased relative to drop heights and number of drops. The fundamental damage of bruise to apples in packages is energy transformation as some of the kinetic energy of drops is absorbed by bruising (Schoorl and Holt, 1982;Holt and Schoorl, 1984;Jarimopas et al, 2007;Zarifneshat et al, 2010).…”
Section: Bruise Sizesupporting
confidence: 93%
“…They proved the usefulness of this method to the precise determination of acting force on the defined contact surface area and its advantage in comparison with well-known methods including force sensors and loaded point. Interesting studies were conducted by Lu et al (2010Lu et al ( , 2012 who used a cling film to measure impact pressure and bruises of apples dropped from different heights and on different surfaces. The applied method and received regression models considering impacted force allowed for evaluation and prediction of apple bruise in terms of the impact loads occurring during transport.…”
Section: Introductionmentioning
confidence: 99%
“…Each fruit was carefully dropped once to land on its equator region by appropriately holding the apple, and was caught immediately after the bounce to avoid additional secondary damage. Similar techniques have been used in the past for drop tests (Jackson & Harker, ; Lu, Ishikawa, Kitazawa, & Satake, ). All drop test apples used including the control were identified and stored at 25 °C for 24 hr for development of the damage and then tested by E‐nose.…”
Section: Methodsmentioning
confidence: 99%